RF22 HIV and type 2 diabetes (T2DM): a qualitative exploration of the burden of care experienced and perceived by persons living with the comorbidities. (September 2018) - Murphy, MM; Greaves, NS; Pooransingh, S; Samuels, TA
Abstract : Background: Research exploring the intersection of communicable and non-communicable diseases, as well as, the lived experiences of persons with multiple chronic morbidities, is limited. This study sought to explore how persons living with HIV (PLHIV) and Type 2 diabetes (T2DM) experience and manage the burden of treatment related to these comorbidities in the context health systems and culture in small island developing states. Methods: Participants with a diagnosis of both HIV and T2DM for more than 2 years were purposively selected with the assistance of HIV treatment centres on the islands of Barbados and Trinidad & Tobago. Twenty individual, face-to-face semi-structured interviews (10 in each country) explored self-care, health care delivery, socioeconomic support and internal resilience. A total of 13 females and 7 males aged 39–65 years were interviewed. All interviews were audio-taped and transcribed verbatim. Data was analyzed using thematic analysis with constant comparison. ATLAS.ti(7) data management software used to manage the data analysis process. Results: Aspects of T2DM self- care such as daily blood glucose monitoring and controlling diet were more onerous than perceived minimal HIV care actions of adhering to oral anti-retroviral therapy ('you just take your medication and go') and clinic visits. While HIV was experienced and perceived as having lower physical workload than T2DM, there was a higher psychological workload throughout the disease trajectory, particularly related to stigma and discrimination in health care settings and in general. T2DM's lower psychological workload was perceived as due to the absence of stigma and discrimination attached to the disease, but adhering to multiple modalities to controll blood glucose increased the physical workload. The impact of having HIV on social determinants such as housing and employment, increased the psychological burden, and impacted on participants' internal resilience. A preference for centralised integrated care (instead of de-centralisation to clinics throughout the health care delivery system), with a more holistic approach within health care settings on both islands was also identified by participants (i.e. having comorbidities such as diabetes also checked and treated at routine HIV clinic visits). Conclusion: Integrated communicable and non-communicable care models which assess both physical and psychological workload should be considered in healthcare, especially since HIV treatment now follows a more chronic treatment pathway. In addition, addressing stigma and discrimination in the general population as well as in health care delivery settings, and their impact on health outcomes for PLHIV, is still an area for public health concern within the Caribbean.